What if … ? A new hypothesis to approach the relationship between environmental stimuli, biological features, and health - Valentina Bollati; Elia Mario Biganzoli; Michele Carugno (Heliyon, 2023)
The ''exposome'' covers all disease determinants across a lifetime. Many exposome factors could induce epigenetic changes, especially in DNA methylation. Yet, the role of these modifications in disease development remains partly understood.Although the possible relationship among the exposome factors, epigenetic modifications, and health/disease has been investigated extensively, all previous studies start from the assumption that epigenetic changes are always detrimental to (or represent an adverse effect on) the health of the affected individual. We hereby propose a new approach to investigate these modifications, and their possible relation with human health, in the context of the exposome.Our hypothesis is based on the possibility that some environmentally-induced changes are plastic entities, responding physiologically to the environment to allow individual adaptation. Briefly, after evaluating the association between environmental exposure and the variation of a given biological parameter through regression models, we use the estimated regression function to predict values for each study subject. We then calculated the relative percent difference (PD) between the measured (i.e., observed) biological parameter and the predicted (i.e., expected) from the model. Notably, we have tested our hypothesis using two distinct models, specifically focusing on LINE-1 methylation and extracellular vesicles (EVs). We hypothesize that the greater the difference between the observed and the expected, the greater the inability of the subject to adapt to external stimuli.